2018
DOI: 10.3390/rs10060874
|View full text |Cite
|
Sign up to set email alerts
|

Operational Built-Up Areas Extraction for Cities in China Using Sentinel-1 SAR Data

Abstract: Abstract:To obtain accurate information in a timely manner on built-up areas (BAs) is essential for urban planning and natural hazard (e.g., earthquakes) response strategies. In this paper, a new method for BAs extraction using the Sentinel-1 SAR is proposed, which includes two steps: (1) Candidate BAs are first selected as seeds from images that show high backscattering and obvious textural patterns, as characterized by image intensity, Getis-Ord index, and the variogram texture features; (2) region growing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Built-up areas in SAR images appear heterogeneous, with alternating brightness and darkness due to the double bounce reflection of buildings, the shadow effect, and multiple reflections [38,39]. As far as building change detection is concerned, it is necessary to add more information to DI and then apply image enhancement to enlarge differences between different building changes (e.g., water to buildings, land to buildings, buildings to land, buildings to water, and so on).…”
Section: Methodsmentioning
confidence: 99%
“…Built-up areas in SAR images appear heterogeneous, with alternating brightness and darkness due to the double bounce reflection of buildings, the shadow effect, and multiple reflections [38,39]. As far as building change detection is concerned, it is necessary to add more information to DI and then apply image enhancement to enlarge differences between different building changes (e.g., water to buildings, land to buildings, buildings to land, buildings to water, and so on).…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that the integrative use of optical and SAR data improved the identification of buildings in less-dense urban areas. The sensitivity of SAR backscatter to building structures can help distinguish bare lands or sparse vegetated lands from built-up areas which are often confused in multispectral images [52]. By fusing the urban mapping results with four available products with a majority voting method, the BTH_BU takes advantage of different data products, and thus improved the accuracy of the final classification results.…”
Section: Urban Growth Analysismentioning
confidence: 99%
“…In 2015, Ban et al [1] developed an urban extraction method named the KTH-Pavia Urban Extractor, which involves image preprocessing, feature enhancement, post-processing, and final decision level fusion using the Sentinel-1 (S1) SAR data. In 2018, Cao et al [22] introduced the use of the image intensity, Getis-Ord index, and the variogram texture features from Sentinel-1 SAR images to extract the candidate Bas, which are regarded as seeds. Then region growing is performed for each seed to extract the Bas.…”
Section: Introductionmentioning
confidence: 99%